Research on Mobile Internet Data Visualization Technology and Application - Qing Zhang; Caixia Tao; Chong Chen (Dianxin kexue)
Big data era brings more opportunities and challenges to the telecom operators. In order to effectively support the accurate analysis and decision making, visualization technology is in urgent need of large data to extracting useful information from the increasingly large data quickly. The features of new technology of mobile internet data visualization were summarized, and combined with typical scenes of more mobile internet customer portrait, practical application of data visualization technology was deeply discussed.